Synchronous ipsilateral conventional renal cell and transitional cell carcinoma - (:unkn) unknown (My University, 2004)
Simultaneous occurrence of renal cell carcinoma (RCC) and transitional cell carcinoma (TCC) in the same kidney is unusual. We report a 61-year-old man with ipsilateral synchronous renal adenocarcinoma and renal pelvic TCC. He was referred to our department for gross hematuria and right flank pain. CT and MRI studies revealed a 57 × 50 mm irregular and infiltrative upper right kidney mass with necrotic components. A right radical nephrectomy was done. Pathological diagnosis was a high grade tumor originating from just beneath the intact urothelium of renal pelvis and infiltrating through the parenchyma showing solid and occasional tubular growth patterns. A second tumor in close proximity to the first was reported as well differented RCC. This is a rare case of combined renal malignancies. © 2004 Kluwer Academic Publishers.
Keywords: Renal cell carcinoma; Synchronous; Transitional cell carcinoma